CLONING AND EXPRESSION OF DNAK GENE ISOLATED FROM LOCAL ISOLATE OF E. COLI RU-3 IN BL21 CELL - Rihab H. Zghair; A.H. Ad’hiah; G.M. Aziz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A set of 60 samples were collected from different sources of multiple areas of Hyderabad (India) in order to select a local Escherichia coli isolates that have the ability to produce HSP70. 26 isolates were characterized after studied the morphological characteristics and microscopic properties of the isolates on macConkey agar and EMB recorded after 24hr. and grams staining was done. The isolated bacteria were screened for various biochemical tests to get 11 isolates that submitted for molecular identification, and the amplification of 16S rRNA regions using universal primer (16S rDNA) verified only 5 E. coli isolates which were sequenced and NCBI accession numbers were acquired. Five distinct isolates (RU-1, RU-3, RW-1, RS-4, and RF-3) of the gene dnaK and its surrounding area were successfully amplified in order to isolate the dnak gene, which encodes the DnaK protein. Amplicons’ nearly identical sequences were discovered by restriction fragment length polymorphism (RFLP). The dnak gene from one representative, RU-3 isolate with accession number OL741466 isolated from Urine samples from suspected urinary tract infection (UTI) patients of Sir Ronald Ross Institute of Tropical and Communicable Diseases Nallakunta, Hyderabad, India was successfully cloned and sequenced by overlapping using 3 set of primers. The 1850 bp long dnaK gene encodes a polypeptide of 607 residues of amino acids. Using pBAD TOPO TA expression systems, the dnaK gene of RU-3 was cloned and expressed in E. coli BL21 (DE3). Incubating the BL21 with different concentrations of isopropyl-β-D-thiogalactopyranoside (IPTG) allowed the grown E. coli to determine the optimum concentration which was 0.05mM to induce the production of recombinant HSP70 protein within 5 hr. which considered as the best expression time in this study.